ECB monetary operations and the interbank repo market - Peter G. Dunne; Michael J. Fleming; Andrey Zholos (Federal Reserve Bank of New York, 2013)
We examine the relationship between monetary policy operations and interbank borrowing and lending of funds using sovereign bonds as collateral. We first establish that, in the precrisis period, there are important but rather weak relations between these funding sources and that this relationship varies within maintenance periods and at the end of the year. Official funding conditions did not meaningfully constrain repo market activity in the 2003-05 period but, in the immediate precrisis period, rate increases led to a sharp contraction in repo activity. Focusing on the crisis period, we identify potentially benign substitution effects between official auctions and repo market activity but our empirical analysis shows that positive innovations in the cost of official funding, due to aggressive bidding, and a limited allotment response, encouraged increased use of the interbank repo market. The analysis informs a discussion of the merits of returning to variable rate operations.
Keywords: E43; E44; E52; E53; G12; G14; 330; repo; funding; liquidity; monetary policy; reserve management